Southesast Asian Proto-Pan-Islamism: A Preliminary Remark of The Genealogy of Muslim Cosmopolitanism in Aceh - Saifuddin Dhuhri (Al-Jami'ah: Journal of Islamic Studies, 2025)
While Pan-Islamism is commonly framed as a nineteenth-century political discourse emerging from the Ottoman response to Western imperialism, this article argues that Aceh, a westernmost province of today’s Indonesia, articulated earlier forms of Islamic solidarity that may be considered as a proto-Pan-Islamic imaginaries. Adopting a conceptual-historical and historiographical approach, the study critically synthesizes historical narratives, available in modern scholarship to examine how Acehnese actors positioned their polity within transregional Islamic networks. Rather than claiming the existence of modern Pan-Islamism avant la lettre, the article traces three interrelated dimensions of Aceh’s early Islamic political imagination; cosmopolitan connectivity, transregional Muslim belonging, and resistance to imperial encroachment, shaped through sustained engagements with major Islamic centers such as Mecca, Persia, the Mughal world, and Istanbul. These connections informed Aceh’s political culture, religious authority, and self-representation as a Muslim power in Southeast Asia. In dialogue with Cemil Aydin’s argument that Pan-Islamism and the notion of a unified “Muslim world” crystallized in the nineteenth century, this article suggests that Aceh’s earlier experiences provided historical conditions that later rendered such global Islamic consciousness intelligible. By foregrounding Aceh as an active imperial periphery, the article challenges Eurocentric periodization and recenters Southeast Asia within global Islamic intellectual history.[Meskipun Pan-Islamisme lazim dipahami sebagai sebuah wacana politik abad ke-19 yang muncul dari respons Kesultanan Utsmaniyah terhadap imperialisme Barat, artikel ini berargumen bahwa Aceh, sebuah provinsi di ujung barat Indonesia masa kini, telah mengartikulasikan bentuk-bentuk awal solidaritas Islam yang dapat dipahami sebagai imajinasi proto-Pan-Islamik. Dengan mengadopsi pendekatan konseptual-historis dan historiografis, studi ini secara kritis mensintesis narasi-narasi sejarah yang tersedia dalam kajian ilmiah modern untuk menelaah bagaimana para aktor Aceh memosisikan polities mereka dalam jaringan Islam transregional. Alih-alih mengklaim keberadaan Pan-Islamisme modern sebelum waktunya, artikel ini menelusuri tiga dimensi yang saling berkaitan dari imajinasi politik Islam awal Aceh, yakni konektivitas kosmopolitan, afiliasi Muslim lintas wilayah, dan perlawanan terhadap penetrasi imperial, yang dibentuk melalui interaksi berkelanjutan dengan pusat-pusat Islam utama seperti Mekah, Persia, dunia Mughal, dan Istanbul. Koneksi-koneksi ini membentuk budaya politik Aceh, otoritas keagamaan, serta representasi diri sebagai sebuah kekuatan Muslim di Asia Tenggara. Dalam dialog dengan argumen Cemil Aydin bahwa Pan-Islamisme dan gagasan tentang “dunia Muslim” yang bersatu mengalami kristalisasi pada abad ke-19, artikel ini menunjukkan bahwa pengalaman-pengalaman Aceh pada periode sebelumnya menyediakan kondisi historis yang kemudian membuat kesadaran Islam global semacam itu menjadi dapat dipahami. Dengan menempatkan Aceh sebagai sebuah periferium imperial yang aktif, artikel ini menantang periodisasi Eurosentris dan memusatkan kembali Asia Tenggara dalam sejarah intelektual Islam global.]